2022
DOI: 10.3390/ijerph192113798
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of SARS-CoV-2 Reinfection in Elite Athletes

Abstract: Objectives: The actual frequency and the risk factors of SARS-CoV-2 reinfection is still a matter of intense scientific discussion. In this case series, we report three elite athletes who underwent COVID-19 reinfection with a short time frame. Case presentations: As a part of contact tracing, three speed skaters (22-, 24-, and 29-year-old males) were found to be SARS-CoV-2 positive by polymerase chain reaction (PCR) tests. Later on, only one of the athletes experienced mild symptoms, such as fatigue, loss of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Schwellnus et al associated symptom clustering with different return-to-play times and compared COVID-19 with other acute respiratory illnesses. They found that return-to-play after COVID-19 was significantly longer than in the other group (IQRs 16–40 vs 7–22 days) and, generally, symptom cluster is associated with prolonged missed training times with excess fatigue in particular 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Schwellnus et al associated symptom clustering with different return-to-play times and compared COVID-19 with other acute respiratory illnesses. They found that return-to-play after COVID-19 was significantly longer than in the other group (IQRs 16–40 vs 7–22 days) and, generally, symptom cluster is associated with prolonged missed training times with excess fatigue in particular 43 .…”
Section: Discussionmentioning
confidence: 99%